MODELING AND CONTROLLER DESIGN FOR A COUPLEDTANK LIQUID LEVEL SYSTEM: ANALYSIS & COMPARISON - Md Rozali, Sahazati; Rahmat, Mohd Fua'ad (2008)
The system under investigation is a coupled-tank apparatus which is a laboratory bench top emulation of a common process in industrial control. The basic control principle of the coupled-tank system is to maintain a constant level of the liquid in the tank when there is an inflow and outflow of water in the tank and outflow of water out of the tank respectively. Classification of this system using system identification technique involved the transient response analysis, the pseudorandom binary sequence (PRBS) analysis and the least square method. The main objective of this project is to determine the mathematical model of a coupled-tank system using these techniques. It follows by designing a controller consists of a PID and a Fuzzy Logic controllers for the system. At the final stage of this project, the usage of both controllers in industrial applications is compared and analyzed